Testing and model validation of round rotor synchronous generator (GENROU). (December 2017) - Talpur, Saifal
Abstract: Role of round rotor synchronous generator in renewable and sustainable energy is rapidly growing due to growing demand of energy production from the renewable resources. The less wear and tear, high robustness and accessibility to power electronics deployment (for active/reactive power flows from and to the grid) has increased the scope of round rotor synchronous generators across large onshore and offshore wind farms besides in hydro power plants. In many commercial power modeling softwares, like System Simulator for Engineering (PSS/E), it is quite difficult to write, access, test, evaluate and validate the built-in models. Therefore to avoid these problems and help the researchers in evaluating, testing, modifying, expanding and enabling the power equipment models as user written, it is important that the equivalent models are designed in an accessible and comparable design and simulation environment like Simulink. The work presented in this paper therefore addresses these issues and provide researchers the equivalent PSS/e models of generator, its associated governor and exciter designed and modeled in Simulink environment.